If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.3x = 6.5(10x + 4) Reorder the terms: 3.3x = 6.5(4 + 10x) 3.3x = (4 * 6.5 + 10x * 6.5) 3.3x = (26 + 65x) Solving 3.3x = 26 + 65x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-65x' to each side of the equation. 3.3x + -65x = 26 + 65x + -65x Combine like terms: 3.3x + -65x = -61.7x -61.7x = 26 + 65x + -65x Combine like terms: 65x + -65x = 0 -61.7x = 26 + 0 -61.7x = 26 Divide each side by '-61.7'. x = -0.4213938412 Simplifying x = -0.4213938412
| ln(2x^2+7x-4)=2+ln(x^2+x-12) | | -1+(2t+3)+2(t-3)= | | 7x+5=45+3x | | ln(x)+ln(x-3)=ln(40) | | 6(p-5)-(4p+9)=25 | | 11a+18b+6C+4C-4B-2A= | | 8x+17=25 | | 15-(y+6)=16 | | 2(4a+2)-3(2a-4)= | | -3(x-5)+2(4x-8)=12 | | 2x^2+3x=200 | | 0.5x^2+3x-36=0 | | 2xy-5yx+7= | | 180(3.14)=2(3.14)*10 | | 28=4v-8 | | 60+20x=96+11x | | 7(8)-3(-8)=5 | | 9z-90=-4z-10 | | x+3=-3+x-2+8 | | y=-3(8)+2 | | y=-3(8)x+2 | | y=-3(0)x+2 | | 2(8s+2)-6s=2(5s+4)-13 | | 7x+17=4x+1 | | 12(3x+3)-5(2x-3)=6x-49 | | 0.55x+0.05(10-x)=0.10(-25) | | 9x+10-6x=6x+40 | | -2(x-8)=4(x+1) | | 10x+7+5x=7x+31 | | (t+9)+(4t-15)= | | 17x+4=10-45 | | 12y+8=5y-5 |